Enhancing Student Retention through a College-Level First Year Seminar - Marie T Huff; Nancy Orel; Melissa Burek (Academic Chairpersons Conference Proceedings, 2016)
To augment university wide retention efforts, we developed a unique first-year seminar experience to enhance student interactions with peers, faculty, and staff; increase their sense of belonging; and help them integrate into the college culture. Presenters will share the results and recommendations on how other schools might utilize this initiative.
Keywords: Retention; student coaching; mentorship; advising; curriculum development